A Huge Solitary Fibrous Tumor Localized in the Pancreas: A Young Women - Tasdemir, Arzu; Soyuer, Isin; Yurci, Alper; Karahanli, Ibrahim; Akyildiz, Hizir (JOP. Journal of the Pancreas, 2012)
Context Solitary fibrous tumor is an uncommon spindle cell tumor which were first described in 1931 at pleura; it should be seen rarely in extra-pleural localization. Case report We report the ninth case of pancreatic solitary fibrous tumor in a 24-year-old woman who presented with mild epigastric pain radiating to the back and chronic constipation. Imaging studies confirmed a solitary mass in the epigastric region that begins from posterior of stomach, fills little curvature and extends to pelvis, invades vascular structures by encircling them and extends to retroperitoneal regions that was considered as it may have mesenchymal origin. The patient underwent an enucleation of the mass which was diagnosed as solitary fibrous tumor, supported by immunohistochemical studies showing positivity for CD34, vimentin and SMA. Conclusion There is limited data regarding biological behavior of solitary fibrous tumors with extra-pleural localization, because they are rare tumors. They are generally asymptomatic and slow growing tumors and it is difficult to distinguish them from other mesenchymal tumors. These issues as well as the prior nine cases are discussed.